2008
DOI: 10.5194/angeo-26-3159-2008
|View full text |Cite
|
Sign up to set email alerts
|

Locating the solar source of 13 April 2006 magnetic cloud

Abstract: Abstract. Using Advanced Composition Explorer (ACE) in situ data we identify and describe an interplanetary magnetic cloud (MC) observed near Earth on 13 April 2006. We also use multi-instrument and multi-wavelength observations from the Solar and Heliospheric Observatory (SOHO), the Transition Region and Coronal Explorer (TRACE) and ground-based solar observatories to determine the solar source of this magnetic cloud.A launch window for the MC between 9 and 11 April 2006 was estimated from the propagation tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…[8] Vertical dot-dashed black lines indicate the boundaries of the magnetic cloud at WIND, which are found to be very similar to those determined by Steed et al [2008], using data from the ACE spacecraft. Unusual magnetic field and plasma observations persist beyond the identified rear boundary of this magnetic cloud and we suggest that this may be the result of interaction between the magnetic cloud flux rope and the solar wind.…”
Section: Overview Of the Eventsupporting
confidence: 48%
See 4 more Smart Citations
“…[8] Vertical dot-dashed black lines indicate the boundaries of the magnetic cloud at WIND, which are found to be very similar to those determined by Steed et al [2008], using data from the ACE spacecraft. Unusual magnetic field and plasma observations persist beyond the identified rear boundary of this magnetic cloud and we suggest that this may be the result of interaction between the magnetic cloud flux rope and the solar wind.…”
Section: Overview Of the Eventsupporting
confidence: 48%
“…We have shown that the rate of radial expansion of the 13 April 2006 magnetic cloud is small at 1 AU. However, unlike the examples studied by Owens [2009], the angular width of this magnetic cloud is believed to be quite small, because despite originating close to disk center, this CME is not observed by the Large Angle Spectroscopic Coronagraph (LASCO) [Brueckner et al, 1995] onboard the SoHO spacecraft [Steed et al, 2008]. Owens [2009] also hypothesise that magnetic reconnection occurring across such current sheets in magnetic clouds may result in a single flux rope being fragmented into multiple, smaller flux ropes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations